Validation and Testing of Novel Underwater Sensors at the Hydrothermal Vent Field of Milos - Siltzovalis, Georgios; Madesis, Ioannis; Lagaki, Varvara; Krassakis, Pavlos; Nikolopoulos, Konstantinos; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2024)
A prototype mobile underwater CdZnTe-based spectrometer was tested under realistic environmental conditions under the scope of the RAMONES Research Programme. Field measurements took place on the island of Milos, which is characterized by the extended hydrothermal vents. A combination of static and dynamic in situ measurements along with analysis of sand and sediment samples, allowed for evaluation of the instrument and will guide its ongoing optimization. Furthermore, a prototype Risk Information System is being developed, allowing easy access for the local stakeholders and scientific community to radioactivity data collected from the instruments of RAMONES.